In vitro effect of IL-2 in combination with pazopanib or sunitinib on lymphocytes function and apoptosis of RCC cells. (August 2014) - Shablak, Alaaeldin; Gilham, David E; Hawkins, Robert E; Elkord, Eyad
Abstract : Objective: Combination of immunotherapy with tyrosine kinase inhibitors (TKIs) has been used with some success for the treatment of metastatic renal cell carcinoma. Herein we evaluate the in vitro effect of high-dose interleukin-2 (HDIL-2) and pazopanib or sunitinib on the lymphocyte function and on induction of apoptosis in renal cell carcinoma (RCC) cell lines. Methods: Peripheral blood mononuclear cells (PBMCs) isolated from healthy donors or RCC patients were treated with different HDIL-2/TKI combinations. Effects of different combinations on proliferation and cytotoxic activity of PBMCs were evaluated, in addition to their effect on apoptosis of three different RCC cell lines. Results: While sunitinib did not inhibit the proliferation of various immune cells induced by HDIL-2, pazopanib appeared to inhibit the HDIL-2–induced proliferation of these cells. Interestingly, none of the HDIL-2/TKI combinations appeared to compromise the functional properties of these cells. Additionally, significant proportion of RCC cell lines treated with pazopanib alone underwent apoptosis, while the proportions of apoptotic cells post-HDIL-2 or sunitinib were not different from the background. Furthermore, the combination of HDIL-2/pazopanib did not inhibit the pazopanib-induced RCC apoptosis. Conclusion: The combination of HDIL-2 with either pazopanib or sunitinib exerts different anticancer mechanisms that could enhance the treatment efficacy.